THE IRRATIONALITY OF RELIGIOUS BELIEF. Issue 42 (9th December 2015) - Frances, Bryan
Abstract : Many highly educated people think religious belief is irrational and unscientific. If you ask a philosopher, however, you'll likely get two answers: most religious belief is rational in some respects and irrational in other respects. In my previous essay ( THINK 40) I explained why they think so many religious beliefs are rational. In this essay I explain why they think those same beliefs are irrational.